[18F]FDG PET/CT versus [18F]FDG PET/MRI in staging of non-small cell lung cancer: a head-to-head comparative meta-analysis - Yu, Dandan; Chen, Chaolin (Frontiers in Medicine, 2025)
PurposeThis meta-analysis aims to compare the diagnostic efficacy of [18F]FDG PET/CT and [18F]FDG PET/MRI in patients with non-small cell lung cancer (NSCLC).MethodsAn extensive literature search was conducted throughout the PubMed, Embase, and Web of Science databases for works accessible through September 2024. We included studies assessed the diagnostic efficacy of [18F]FDG PET/CT and [18F]FDG PET/MRI in NSCLC.ResultsThe meta-analysis includes six studies with a total of 437 patients. The sensitivity and specificity of [18F]FDG PET/CT and [18F]FDG PET/MRI for detecting lymph node metastasis were similar, at 0.82 (0.68–0.94) vs. 0.86 (0.70–0.97) and 0.88 (0.76–0.96) vs. 0.90 (0.85–0.94), respectively, with no significant differences (p = 0.70 for sensitivity, p = 0.75 for specificity). For distant metastasis, the sensitivity of [18F]FDG PET/CT and [18F]FDG PET/MRI was 0.86 (0.60–1.00) and 0.93 (0.63–1.00), and specificity was 0.89 (0.65–1.00) vs. 0.90 (0.64–1.00), respectively, also showing no significant differences (p = 0.66 for sensitivity, p = 0.97 for specificity).ConclusionOur meta-analysis shows that [18F]FDG PET/MRI has similar sensitivity and specificity to [18F]FDG PET/CT in identifying lymph node and distant metastases in patients with NSCLC. Additional larger sample prospective studies are needed to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023479817, CRD42023479817.